2012
DOI: 10.21273/hortsci.47.10.1457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Source on Pac Choi (Brassica rapa L.) Chemistry and Interactions with the Diamondback Moth (Plutella xylostella L.)

Abstract: Two greenhouse studies were conducted to examine effects of nitrogen source on primary and secondary metabolism of pac choi (Brassica rapa L. subsp. chinensis cv. Mei Qing Choi) and diamondback moth (Plutella xylostella L.) consumption, development, survival, and body weight. Applications of a liquid organic source of nitrogen (fish hydrolysate fertilizer) were compared with a conventional fertilizer to determine whether n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
10
0
3
Order By: Relevance
“…Similar results were also observed in Komatsuna amended with commercial compost under single and triple application rates of N:P:K (R15 and R16). This showed rapid response on plant growth towards compost fertilizer might not be instant as seen in many inorganic N-fertilizer studies (13,(17)(18).…”
Section: Growth Promotion Of Afm Compost On the Cultivation Of Brassimentioning
confidence: 67%
See 1 more Smart Citation
“…Similar results were also observed in Komatsuna amended with commercial compost under single and triple application rates of N:P:K (R15 and R16). This showed rapid response on plant growth towards compost fertilizer might not be instant as seen in many inorganic N-fertilizer studies (13,(17)(18).…”
Section: Growth Promotion Of Afm Compost On the Cultivation Of Brassimentioning
confidence: 67%
“…Then the residual precipitate, described as anaerobically fermented MKR (AFM) compost, was tested for its plant growth promotion activity by incorporating it into planting medium as soil amendment material. Since screening test on the growth performance of Zea mays (monocotyledon, C4 plant) was previously performed, we further investigate plant growth promoting effect of strain KBKU21 on Brassica rapa (dicotyledon, C3 plant) based on the fact that it is widely used in evaluating growth performance respond under different fertilizer rates and fertilizer types (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…La reducción de la duración larval también la observaron Boiteau et al (2008) en la larva de la catarinita de la papa (L. decemlineata), con la aplicación de altas dosis de abono orgánico respecto a la aplicación de fertilizantes minerales; pero el abono también puede incrementar la duración larval, como en la mariposita blanca de la col P. rapae crucivora (Hsu et al, 2009) y en la palomilla dorso de diamante (P. xylostella) (Johnson et al, 2012) En lo que respecta al daño diario del adulto en función de la fertilización, éste varió de 0.8cm 2 en composta 3t ha -1 (sin fertilización mineral ni agronosode) a 3.6cm 2 en fertilizante mineral 40-20-10 (sin composta ni agronosode) (Tabla 2), con diferencias estadísticamente significativas entre los tratamientos de composta a 1 y 3t ha -1 contra los de fertilización mineral media y baja y el tratamiento sin fertilizar. Estos datos muestran que cuando se usa composta se reduce el daño del adulto si se aplican dosis cercanas a 3t ha -1 , pudiendo ser mayor a 50% con la aplicación de 1.8 a 3.6t ha -1 , o menor al daño medio en las dosis que se alejan de éstas hacia 0 o 4.5t ha -1 , porque la relación entre aplicación de composta y el daño diario del adulto de conchuela se explica por una ecuación de tercer grado, de acuerdo al análisis de regresión (Figura 1).…”
Section: Resultados Y Discusiónunclassified
“…La fertilización orgánica, a través de abonos, disminuye el daño de la tortuguilla rayada del pepino (Acalymma vittatum), de la diabrótica de once puntos (Diabrotica undecimpunctata), del gusano del cuerno (Manduca quinquemaculata) (Yardim et al, 2006); de la catarinita de la papa (Leptinotarsa decemlineata) (Boiteau, Lynch y Martin, 2008), y del chapulín (Hieroglyphus nigrorepletus) (Dixit, Dixit y Samson 2009). Además, reduce la tasa de crecimiento de la mariposita blanca de la col (Pieris rapae crucivora) (Hsu, Shen y Hwang 2009), y el peso y la supervivencia de la palo-milla dorso de diamante (Plutella xylostella) (Johnson et al, 2012).…”
Section: Introductionunclassified
“…Bloem et al (2007) reported that rapeseed plants fertilized with sulfur were highly resistant to pathogens. Higher rates of sulfur fertilizer (De Pascale et al 2007) and the use of liquid organic nitrogen instead of mineral fertilizer (Johnson et al 2012) led to higher accumulation of phenolic acids (sinapinic, gallic, p-coumaric acids) in Brassicaceae plants in response to biotic stress, including pathogen infections (Mert-Türk et al 2008;Johangir et al 2009). …”
Section: Resultsmentioning
confidence: 99%